2021
DOI: 10.1590/0104-1428.04221
|View full text |Cite
|
Sign up to set email alerts
|

Determination of antioxidant and antimicrobial activity of sweetgum (Liquidambar orientalis) leaf, a medicinal plant

Abstract: In the study, sweetgum tree (Liquidambar orientalis), which is an endemic species that grows in Mugla, Köyceğiz and is applied for medicinal purposes among the public, its leaves was examined. The antioxidant ability of the extract obtained from dried plant leaves has been evaluated using a variety of methods which are Total Phenolic Substance, Total Flavonoid, FRAP, CUPRAC, DPPH, and ABTS + . Simultaneously, the antimicrobial activity of the plant extract was examined using disk diffusion and microdilution me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The reduction ability of gum was 0.91 mmol TE/g in the phosphomolybdenum assay. In a literature review, although we observed several studies on the antioxidant properties of L. orientalis extracts, [20–22] no data were obtained for gum. At this point, the presented results could make valuable contributions to the scientific pool of the Liquidambar genus.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The reduction ability of gum was 0.91 mmol TE/g in the phosphomolybdenum assay. In a literature review, although we observed several studies on the antioxidant properties of L. orientalis extracts, [20–22] no data were obtained for gum. At this point, the presented results could make valuable contributions to the scientific pool of the Liquidambar genus.…”
Section: Resultsmentioning
confidence: 90%
“…Therefore, plant oils and extracts have emerged as promising anticancer therapeutic agents, but their potential has yet to be fully exploited due to their high and complex compositions. The active composition of the plant oils and extracts, mainly phenols, alcohol, terpene compounds, and ketone, can affect cell growth, cycle, and death and could synergistically work [21] …”
Section: Resultsmentioning
confidence: 99%